Surveillance capitalism as white world-making - Yvonne Jooste (Acta Academica, 2021)
The era of ‘surveillance capitalism’ as a new logic of accumulation that claims human experience as free raw material necessitates an understanding of how corporate-controlled digital communication technologies govern and structure how we come to know the world. This article investigates surveillance capitalist operations and argues that it enables (1) algorithmic colonisation, (2) oppressive digital practices that reify bias along racial lines, and (3) the turning of bodies into objects in the creation and maintenance of whiteness. Through presenting these different arguments, a larger point emerges, namely, that surveillance capitalist operations must be understood as intimately tied to the project of white world-making.